A Bis(Boronic Ester)‐Based Fluorogenic and Chromogenic Sensor for F– and Cu2+. Issue 28 (5th October 2017) - Maity, Dinesh; Hari, Nairita; Mohanta, Sasankasekhar
Abstract: In this work, we designed a new boronic ester based ditopic Schiff's base receptor, 2, 2′‐(((1E, 1′E)‐((2, 4, 8, 10‐tetraoxa‐3, 9‐diboraspiro[5.5]undecane‐3, 9‐diyl)bis(4, 1‐phenylene)) bis(me‐thanylylidene))bis(azanylylidene))diphenol (H2 L)by condensing ortho ‐aminophenol, 4‐formyl phenyl boronic acid and pentaerythritol. The receptor has been thoroughly characterized by 1 H, 13 C, 11 B NMR spectroscopy as well as high resolution mass spectroscopy and by elemental analyses. Hydrolytic stability of the receptor was also checked by recording its 1 H NMR spectrum in mixed DMSO‐ d 6 and D2 O solvent. The receptor acts as highly selective and sensitive probe for the detection of Cu 2+ and F – among the studied ions in solution. Both anion and cation sensing studies were thoroughly investigated through multiple optical channels such as UV‐vis absorption and steady state and time‐resolved emission spectroscopic techniques. Among the studied anions, only F – induces color and absorption and emission and time‐resolved emission spectral changes in dimethylsulphoxide.Addition of Cu 2+ ion to the solution of the receptor in dimethylsulfoxide‐water (5:2 v/v) leads to remarkable color and absorption spectral changes. Association constants of the receptor towards F – have been also evaluated from the absorption/emission titration data. Abstract : Boronic ester based receptor acts as chromogenic and flurogenic sensor for Cu 2+ and F – in aqueous and organic media. While an iminophenol moiety interacts with Cu 2+, both the boron centre and a phenol moiety are the centres of sensing of F – .